PENGARUH WAKTU PENGUKUSAN JAGUNG KUNING DAN PEMANASAN SUSU KEDELAI JAGUNG TERHADAP SIFAT FISIKOKIMIA DAN ORGANOLEPTIK PRODUK - Purwanegara, Grace; Trsinawati, Chatarina Yayuk; Srianta, Ignatius (Widya Mandala Surabaya Catholic University, 2013)
The aim of this research is to study the effects of the time of steaming corn and heating treatment on physicochemical and sensory properties of soy-corn milk. Level of the time of steaming corn were 15 minutes, 30 minutes, and 45 minutes while the method of heating soy-corn milk made with pasteurization and sterilization. The results showed that time of steaming corn affects total sugars, protein content, and colloidal stability of soy-corn milk. The longer time of steaming corn, the increased levels of total sugars, protein content, and colloidal stability of soy-corn milk occured. Heating treatment affects total dissolved solids, total sugar content, viscosity and colloidal stability of soy-corn milk. An open heating method of pasteurization produced higher total dissolved solids, total sugar content, viscosity and colloidal stability than those of sterilization method. The time of steaming corn and heating method of soy-corn milk has no effect on appearance and taste preferences.